Komposisi Jenis dan Keanekaragaman Ikan Karang pada 3 Jenis Bahan Terumbu Karang Buatan (Artificial reef) yang Berbeda (Beton, Ban Bekas, dan Besi) di Teluk Jemeluk Amed, Karangasem, Bali - Ida Bagus Indra Danendra; I Gusti Bagus Sila Dharma; Elok Faiqoh (Fakultas Kelautan dan Perikanan Universitas Udayana, 2021)
Artificial reef at Jemeluk Bay, Karangasem, Bali is one of the area’s fisheries potential. Artificial reef is an underwater structure that is made for fishes’ protection and feeding ground. The purpose of this research is to know and understand types of reef fishes that surround the artificial reef, as well as the artificial reef’s affect onto the fish’s abundance at Jemeluk Bay. The method used for reef fish monitoring by visual census at artificial reef made from concrete, rubber tire and steel. This research is done towards six coral reef structures to get the reef fishes composition, which is made out of 7 fish families, 17 species, with an abundance total of 708 individuals. The highest fish abundance was founded at the 2nd rubber tire artificial reef with 6,4 individuals/m2, and the lowest fish abundance was found at the 1st concrete artificial reef with 3,28 individuals/m2. From the calculation at six of the artificial reef structures, the diversity index varies between 1,2 – 1,57, which is categorized as low diversity. The diversity value shows that steel artificial reef have the highest fish species diversity, however is still categorized as low.